Impact of COVID‐19 on the quality of life of patients with neuromuscular disorders in the Lombardy area, Italy. Issue 4 (3rd August 2021) - Gagliardi, Delia; Costamagna, Gianluca; Abati, Elena; Mauri, Eleonora; Brusa, Roberta; Scudeller, Luigia; Andreoli, Luca; Citterio, Gaia; Piccin, Eleonora; Magri, Francesca; Meneri, Megi; Velardo, Daniele; et al.
Abstract: Introduction:/Aims: Patients with neuromuscular disorders (NMDs), including many elderly, immunosuppressed, and disabled individuals, may have been particularly affected during the coronavirus disease 2019 (COVID‐19) pandemic in Lombardy, a COVID‐19 high‐incidence area between February and May 2020. We aimed to evaluate the effects of the COVID‐19 pandemic on the quality of life (QoL) and perceived disease burden of this group of patients. Methods: We conducted a cross‐sectional phone‐based survey study between June 1 and June 14, 2020, on a sample of 240 NMD patients followed at our clinic in Milan, Italy. We asked about perceived NMD burden and QoL before and during the COVID‐19 pandemic. We collected responses on access to outpatient care and ancillary services. We investigated the presence of symptoms suggestive of COVID‐19 infection and confirmed cases. Results: We collected 205 responses: 53 patients (25.9%) reported a subjective worsening of the underlying NMD. QoL measures showed a significant worsening between pre and pandemic time frames (odds ratio, 2.14 95%; confidence interval, 1.82–2.51). Outpatient visits were postponed in more than half of cases (57.1%), with 104 patients (50.7%) experiencing a cancellation of scheduled diagnostic tests. 79 patients (38.5%) reported at least one symptom attributable to COVID‐19 infection. Among the 10 patients tested with nasopharyngeal swabs, 6 tested positive and 3 died from respiratory failure, including 2 patients on corticosteroid/ immunosuppressive therapy. Discussion: The COVID‐19 pandemic affected QoL and limited access to outpatient care and ancillary services of NMD patients in Lombardy between February and May 2020.